Maturity analysis of small companies AEC for the implementation of management by simultaneous engineering - Gevaerd, Paulo Henrique Ferrarini; Romano, Cezar Augusto (Seven Editora, 2024)
The work presents an analysis of maturity in architecture, engineering and construction companies, in relation to the objectives of Simultaneous Engineering. The main objective was to understand the impact on the maturity of small companies in the architecture, engineering and construction industry when using collaborative computational tools in the implementation of Simultaneous Engineering concepts. To develop the research, bibliometric analyses were made to characterize the main authors involved with the themes of Simultaneous Engineering. These authors formed the theoretical basis for the development of the interview protocol in multiple case studies. After the elaboration of the research protocol and its improvement based on a pilot study, interviews were conducted with representatives of nine companies in the sector and from their answers maturity analyses were developed. As a result of the analyses, the following conclusions were obtained: small companies need greater self-knowledge to balance their business maturity; Architecture firms have a different maturity profile from engineering and construction firms, and architecture firms are positively influenced by their tools, engineering and construction firms still have low levels of maturity in these relationships; The tools currently used by companies do not help in the integration of business and intercompany processes, which hinders the implementation of Simultaneous Engineering concepts. DOI:https://doi.org/10.56238/sevened2024.010-031